A Historical Investigation of Sexuality and Marked Space - Case Study: Urban Historical Neighbourhood in Tehran - Mohammadi, Maryam (International Planning History Society Proceedings, 2016)
efore the 1970s, the adoption of an old global hypothesis (i.e. male/female dichotomy, in which different spheres are defined based on gender), was a key reason why the approach to gender justice could not attract attention in urban planning. This hypothesis argued in particular that women belong to the home and internal space and men to the public sphere and external spaces, while planning is to ensure that social justice is established and therefore the attention should inevitably give to the approach of inclusion instead of women’s exclusion. So the main goal of this paper is to discuss the concept of gender, justice, and gender justice and also present the approach of women’s inclusion vs. women’s exclusion through history of urban planning. For this investigation two urban planning models (the traditional urban planning model- comprehensive plan and the strategic urban planning model) have selected and deeply examined. For better understanding of the influences of urban planning models on producing the gendered marked space or a responsive space, neighbourhood scale as the main space of women’s presence has chosen in Tehran. Since the historical development is an important consideration in this study, Chizar neighbourhood is chosen as an appropriate case because of its long history and religious identity, and also the changes created during the process of urban development plans in Tehran. Therefore, it provides an ideal text for evaluating the level of gender justice in the context of traditional structure of Iranian neighbourhoods. This study is an applied research of descriptive-analytical nature, in which the in-depth interview was used as the data collection method and the sample size was 30. Women’s narrations about their everyday space are considered as a measure to analyse markedness, which serves as the basis for identifying dichotomies or binary oppositions that are affected by the old male/female dichotomy. The results showed that the historical neighbourhoods changed during the urban development process in Tehran have failed to respond to gender justice concerns and, compared to previous models, sometimes have worked more inappropriately and desirably in the views of women.